Full genome analysis of rotavirus G9P[8] strains identified in acute gastroenteritis cases reveals genetic diversity: Pune, western India. Issue 8 (14th March 2017) - Tatte, Vaishali S.; Chaphekar, Deepa; Gopalkrishna, Varanasi
Abstract : Group A rotaviruses (RVA) are the major enteric etiological agents of severe acute gastroenteritis among children globally. As G9 RVA now represents as one of the major human RVA genotypes, studies on full genome of this particular genotype are being carried out worldwide. So far, no such studies on G9P[8] RVAs have been reported from Pune, western part of India. Keeping in view of this, the study was undertaken to understand the degree of genetic diversity of the commonly circulating G9P[8] RVA strains. Rotavirus surveillance studies carried out earlier during the years 2009‐2011 showed increase in the prevalence of G9P[8] RVAs. Representative G9P[8] RVA strains from the years 2009, 2010, and 2011 were selected for the study. In general, all the G9 RVA strains showed clustering in the globally circulating sublineage of the VP7 gene and showed nucleotide/amino acid identities of 96.8‐99.7%/96.9‐99.8% with global G9 RV strains. Full genome analysis, of all three RVAs in this study indicated Wa‐like genotype constellation G9‐P[8]‐I1‐R1‐C1‐M1‐A1‐N1‐T1‐E1‐H1. Within the strains nucleotide/amino acid divergence of 0.1‐3.4%/0.0‐4.1% was noted in all the RVA structural and non‐structural genes. In conclusion, the present study highlights intra‐genotypic variations throughout the RVA genome. The study further emphasizes the need for surveillance and analysis of the whole genomic constellation of the commonly circulating RVA strains of other regions in the country for understanding to a greater degree of the impact of rotavirus vaccination recently introduced in India.